2013
DOI: 10.1021/pr400050u
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1 Deficiency Is Associated with Severe Liver Steatosis in Mice Fed a High-fat High-cholesterol Diet: A Metabolomic Approach

Abstract: Oxidative stress is a determinant of liver steatosis and the progression to more severe forms of disease. The present study investigated the effect of paraoxonase-1 (PON1) deficiency on histological alterations and hepatic metabolism in mice fed a high-fat high-cholesterol diet. We performed nontargeted metabolomics on liver tissues from 8 male PON1-deficient mice and 8 wild-type animals fed a high-fat, high-cholesterol diet for 22 weeks. We also measured 8-oxo-20-deoxyguanosine, reduced and oxidized glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…The HF rats also showed reduced serum and liver PON1 activity. These findings corroborate with García-Heredia et al [25] that showed that PON-deficient mice fed a high-fat high-cholesterol diet presented significant alterations in liver tissues, such as increased hepatic steatosis and the expression of makers of oxidative stress and inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The HF rats also showed reduced serum and liver PON1 activity. These findings corroborate with García-Heredia et al [25] that showed that PON-deficient mice fed a high-fat high-cholesterol diet presented significant alterations in liver tissues, such as increased hepatic steatosis and the expression of makers of oxidative stress and inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…PON1 levels significantly decreased in serum of patients with chronic liver diseases such as NAFLD, hepatitis, and cirrhosis [13, 24]. More relevantly, PON1-deficient mice fed a high-fat high-cholesterol diet showed histological alterations in the liver, suggesting that PON1 plays a major role in protection against oxidative stress on diet-induced fatty liver [25]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, PON1 deficient mice have been shown to be more susceptible to lipoprotein oxidation, inflammation, atherosclerosis [12, 13, 27], and hepatic steatosis [28], whereas PON1 transgenic mice over-expressing human PON1 are more resistant to inflammation and atherosclerosis [14]. PON1 has been shown to prevent LDL oxidation in vitro [18, 19] and decreased levels of PON1 are associated with increased risk for cardiovascular disease in humans [7, 2932].…”
Section: 1 Introductionmentioning
confidence: 99%
“…PON1-deficient mice are found to have decreased glycolysis [18]. Glucose-enrichment invariably regulated PON1 expression while glucose-starvation recovered the expression in A549 cells (Figure 6A, 6B) while no regulation was observed in L132 cells (data not shown).…”
Section: Resultsmentioning
confidence: 93%